Selective 1, 3-butadiene hydrogenation by gold nanoparticles deposited & precipitated onto nano-carbon materials. Issue 99 (24th September 2015) - Castillejos, E.; Bachiller-Baeza, B.; Asedegbega-Nieto, E.; Guerrero-Ruiz, A.; Rodríguez-Ramos, I.
Abstract : GO and multiwall CNTs were modified by treatment with urea and annealing at different temperatures incorporating N adatoms. AuGO and AuCNT catalysts were prepared and their activity depended on the Au NP size and the characteristics of the support. Abstract : Graphene oxide and multiwall carbon nanotubes (CNTs) were chemically modified by treatment with urea and subsequent annealing at different temperatures. These materials were used as supports for gold nanoparticles and the resulting samples have been applied as catalysts in the 1, 3-butadiene partial hydrogenation reaction. The supports and catalysts were exhaustively characterized. It was shown that urea treatments modified the graphene surfaces and the morphology of CNTs, in both cases with incorporation of significant amounts of different nitrogen surface groups. The presence of these groups on few layered graphene or on CNT surfaces modifies the gold precipitation–deposition process during catalyst preparation, giving place to different amounts of incorporated gold on the various supports. The obtained catalytic results suggested that the partial hydrogenation requires limited availability of hydrogen, and for this the migration through adsorbed species between the metal and support to initiate the hydrogenation, probably by a spillover mechanism, seems to be a required step. In general intramolecular selectivity is structure-sensitive meanwhile catalytic activity is not structure-sensitive, as evidenced when the gold nanoparticle sizes are decreased.